Effect of Life Style and Eating Habits on Blood Lipid Levels - YAZAR , H.; TIFTIK, A.M. (Asian Journal of Chemistry, 2010)
The represented study has been commenced on 1006 adult people consists of 598 women and 408 men between age of 25-55 from Cumra Government Hospital, Turkey about the effect of life style and eating habit on their blood lipid levels. Blood samples taken after 12 h fasting patients were kept into tubes. After coagulation, triglyceride, total cholesterol, low density lipoprotein cholesterol and high density lipoprotein cholesterol analysis were completed by separation serums. The average triglyceride levels of 1006 adult people is found to be 167.80 ± 98.43 mg/dl, triglyceride levels of men is 174.37 ± 102.69 mg/dl and for women is 163.31 ± 95 mg/dl. While overall average total cholesterol is 196.66 ± 44.93 mg/dl, in men is 191.76 ± 43.55 mg/dl and it is found in women as 200.00 ± 45.59 mg/dl. Average high density lipoprotein cholesterol in general is 50.67 ± 12.30mg/dl, in men is 48.11 ± 12.59 mg/dl and in women is 52.41 ± 11.80 mg/dl. The mean low density lipoprotein is 115.49 ± 38.52 mg/dl, in men is 112.23 ± 36.19 mg/dl and in women is 117.71 ± 39.90 mg/dl. This study results in life styles groups; L0: 101 adult polyclinic patients, L1: 195 adult polyclinic patients, L2: 354 adult polyclinic patients, L3: 356 adult polyclinic patients. In this study results in eating habits groups; E0: 210 adult polyclinic patients, E1: 187 adult polyclinic patients, E2: 214 adult polyclinic patients, E3: 395 adult polyclinic patients. In this study with eating habits connection life style are significant (p < 0.05 ). Triglyceride and high density lipoprotein values that the high are determined and this situation are interpreted that life styles c on lipid profile of the positive effect (p < 0.05).